1973
DOI: 10.1103/physrevlett.30.1116
|View full text |Cite
|
Sign up to set email alerts
|

Neutron Emission from Laser-Produced Plasmas

Abstract: can make an order-of-magnitude estimate of r using a classical hard-sphere model for the collisions where the rotons are assumed to be stationary, and the He^ quasiparticles move with a mean speed {v) = {^kT/m^''Y''^, Thenwhere r'Ms the mean collision frequency, n is the number density of atoms, and m^'^-^2,Zm^ is the effective mass of the He^ quasiparticle. Using a value ofa = 1.6xl0"^^ cm^ measured by Herzlinger and King,^ this expression becomes r(°K) = 5.7X, in satisfactory agreement with our results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

1974
1974
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(12 citation statements)
references
References 12 publications
0
11
1
Order By: Relevance
“…Recent experiments of laser-pellet interactions 1 have demonstrated the existence of energetic ions of 10-30 keV which carry approximately half the energy absorbed by the plasma. These energetic ions could also be important in explaining the observation of neutrons.…”
Section: Ion Acceleration In Strong Electromagnetic Interactions Withmentioning
confidence: 99%
“…Recent experiments of laser-pellet interactions 1 have demonstrated the existence of energetic ions of 10-30 keV which carry approximately half the energy absorbed by the plasma. These energetic ions could also be important in explaining the observation of neutrons.…”
Section: Ion Acceleration In Strong Electromagnetic Interactions Withmentioning
confidence: 99%
“…Experimental efforts to optimize laser-based neutron generators have been reported for over four decades [6][7][8][9]. Two experiments in the past year [4,10,11] reported lasergenerated neutron yields as high as 10 10 n/sr per laser shot.…”
Section: Pacsmentioning
confidence: 99%
“…McCall et al 76 at Los Alamos argued that the neutrons could be produced in the blowoff plasma by fast ions generated through electrostatic acceleration. They showed that neutrons could arise from deuterium monolayers deposited on the chamber wall.…”
Section: A the Quest For Neutronsmentioning
confidence: 99%
“…They showed that neutrons could arise from deuterium monolayers deposited on the chamber wall. They obtained neutrons using a short-pulse laser (17 J, 25 76 that in the case of tight focusing on a solid target, the neutrons were produced external to the plasma from accelerated deuterons. However, they found that in a multibeam irradiation geometry with spherical targets, the neutrons were thermal, on the basis of the width of the energy spectrum of the neutrons.…”
Section: A the Quest For Neutronsmentioning
confidence: 99%